PENGARUH PENGGUNAAN MEDIA INTERAKTIF WEB GOOGLE SITES TERHADAP HASIL BELAJAR SISWA PADA MATERI PECAHAN DI KELAS IV SD NEGERI 2 PAGAR AIR ACEH BESAR - Nadif, Deo Iksan; Vitoria, Linda; Fitri, Aida (STKIP Subang, 2026)
The utilization of technology in learning is one of the efforts to improve the quality of the learning process and students’ learning outcomes. Web-based learning media, such as Google Sites, enable the presentation of materials in a more interactive and engaging way, helping students understand abstract mathematical concepts such as fractions. This study aims to determine the effect of using Google Sites web-based interactive media on students’ learning outcomes in fraction material for fourth-grade students at SD Negeri 2 Pagar Air, Aceh Besar. This study employed a quantitative approach with a pre-experimental design using a one-group pretest–posttest design. The sample consisted of 22 fourth-grade students. Data were collected through learning outcome tests in the form of pretest and posttest. Data analysis was conducted using a paired sample t-test to determine the difference in students’ learning outcomes before and after the use of the media. The results of data analysis showed that the significance value (Sig. 2-tailed) was 0.000 < 0.05, indicating a significant difference. Therefore, Ha was accepted and H₀ was rejected. It can be concluded that the use of Google Sites web-based interactive media has a significant effect on improving students’ learning outcomes in fraction material. This study recommends the use of web-based learning media in the mathematics learning process in elementary schools.